Cover Picture: Cascade Syntheses Routes to the Centrocountins (Chem. Eur. J. 7/2013). Issue 7 (1st February 2013) - Eschenbrenner‐Lux, Vincent; Dückert, Heiko; Khedkar, Vivek; Bruss, Hanna; Waldmann, Herbert; Kumar, Kamal
<x xml:space="preserve">Abstract</x> The longest cascade reaction sequence known to date provides natural‐product‐inspired and biologically active centrocountins, or tetrahydroindoloquinolizines and related molecules. K. Kumar, H. Waldmann et al. unravel mechanistic insights into this long cascade reaction sequence in their Full Paper on page 2294 ff. by isolating and characterizing various intermediates and with control experiments. The cover picture shows a natural setup as a symbolic source of inspiration. As the reaction substrates in the pool of water flow in different streams, representing different cascade reaction sequences, they are progressively transformed into different intermediates before settling as a collection of products, the tetrahydro(indolo)quinolizine molecules.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>